2017
DOI: 10.1590/0037-8682-0138-2017
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey of Leptospira spp. and Toxoplasma gondii in rats captured from two zoos in Southern Brazil

Abstract: Introduction: Norway rats (Rattus norvegicus) are zoonotic reservoirs for Leptospira spp. and Toxoplasma gondii, and infl uence diseases in urban areas. Methods: Free-ranging and laboratory-raised rats from two zoos in southern Brazil were tested for Leptospira spp. and T. gondii using microscopic agglutination and modifi ed agglutination tests, respectively. Results: Overall, 25.6% and 4.6% free-ranging rats tested positive for Leptospira spp. and T. gondii, respectively, with co-seropositivity occurring in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
2
9
0
1
Order By: Relevance
“…Although not frequently reported, strains of L. noguchii have been described infecting a variety of animal hosts, including cattle (Barragan et al, ; Faine et al, ; Hamond et al, ; Martins et al, ; Zarantonelli et al, ), rats (Pellizzaro et al, ; Vieira et al, ) and bats (Ballados‐González et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although not frequently reported, strains of L. noguchii have been described infecting a variety of animal hosts, including cattle (Barragan et al, ; Faine et al, ; Hamond et al, ; Martins et al, ; Zarantonelli et al, ), rats (Pellizzaro et al, ; Vieira et al, ) and bats (Ballados‐González et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…They revealed that the frequency of Toxoplasma gondii in the Rattus norvegicus population in Argentina and China was 32.8% and 23.9%, respectively [24,25]. However, Pellizzaro et al in Brazil [8], Saki et al from Ahvaz province of Iran [10], Gennari from Brazil [9], and Cheng Yin from China [26] showed that the frequency of Toxoplasma gondii in Rattus population was 4.6%, 6%, 8.6%, and 3.2%, respectively. Generally, the high frequency of Giardia spp and Toxoplasma gondii in the Rattus population in Tehran is an important concern.…”
Section: Discussionmentioning
confidence: 99%
“…In urban areas, Rattus norvegicus act as a reservoir of zoonotic pathogens, especially zoonotic parasites, and hold a connection to various important hygienic problems; they are also responsible for human morbidity and mortality, worldwide [7]. Many of these zoonotic parasites including Leishmania spp, Giardia spp, Toxoplasma gondii, Trichomonas vaginalis, and Cryptosporidium spp are assumed to be endemic in Rattus norvegicus populations around the world [8,9,10,11]. Currently, approximately seventy-nine species of rodents have been recognized in Iran; among these previously identified rodents, Rattus norvegicus have shown greater frequency in the urban area and occupied widespread habitats in cities [12].…”
Section: Introductionmentioning
confidence: 99%
“…We also identified both species from environmental samples suggesting the role of the environment in the spread of this pathogen. Strains of L. noguchii have been described infecting cattle [ 19 , 20 , 21 , 22 ] rats [ 23 , 24 ] and bats [ 25 ]. Apart from animal infections, the zoonotic aspect of this species has been suggested.…”
Section: Discussionmentioning
confidence: 99%